The Influence of Ownership on Capital Structure Of Companies Listed In Indonesia Stock Exchange (IDX) - Desi Ilona; Titami Seprianti; Hilda Mary (UPI YPTK Journal of Business and Economics, 2021)
The purpose of this research is to analyze the effect of foreign, institutional, and family ownership on capital structure. The two control variables include company size and profitability, while the secondary data were obtained from the financial firm, and 2014-2018 annual report. Sampling technique by using total sampling method. A total of 197 companies listed on the Indonesia Stock Exchange (IDX) were sampled. Data analysis by used descriptive analysis, classic assumption test and pane data regression. The results showed that foreign, institutional, and family ownerships have no significant effect on capital structure. However, firm size and profitability have positive and negative significant effects on capital structure, respectively.